Transcriptome response of proliferating muscle satellite cells to thermal challenge in commercial turkey - Reed, Kent M.; Mendoza, Kristelle M.; Strasburg, Gale M.; Velleman, Sandra G. (Frontiers in Physiology, 2022)
Thermal stress poses a threat to agricultural systems through increased risk to animal growth, health, and production. Exposure of poultry, especially hatchlings, to extreme temperatures can seriously affect muscle development and thus compromise subsequent meat quality. This study was designed to characterize transcriptional changes induced in turkey muscle satellite cells (SCs) cultured from commercial birds under thermal challenge to determine the applicability of previous results obtained for select research lines. Satellite cells isolated from the pectoralis major muscle of 1-wk old commercial fast-growing birds (Nicholas turkey, NCT) and from a slower-growing research line (RBC2) were proliferated in culture at 38°C or 43°C for 72 h. RNAseq analysis found statistically significant differences in gene expression among treatments and between turkey lines with a greater number of genes altered in the NCT SCs suggesting early myogenesis. Pathway analysis identified cell signaling and regulation of Ca2+ as important responses. Expression of the intercellular signaling Wnt genes, particularly Wnt5a and 7a was significantly altered by temperature with differential response between lines. The peripheral calcium channel RYR3 gene was among the genes most highly upregulated by heat stress. Increased expression of RYR3 would likely result in higher resting cytosolic calcium levels and increased overall gene transcription. Although responses in the calcium signaling pathway were similar among the RBC2 and NCT lines, the magnitude of expression changes was greater in the commercially selected birds. These results provide evidence into how SC activity, cellular fate, and ultimately muscle development are altered by heat stress and commercial selection.